Combination of local sea winds/land breezes and nearshore wave energy resource: Case study at MaRELab (Naples, Italy). (1st April 2022) - Contestabile, Pasquale; Russo, Sara; Azzellino, Arianna; Cascetta, Furio; Vicinanza, Diego
Highlights: Effects of local meteorological patterns (due to nearshore conditions) in wave and wind resources. Procedure to estimate the quality of the co-exploitation by means of different multivariate techniques. Methodology to define complementarity, combination and misalignment for co-developing wind-wave projects at nearshore locations. Non-canonical design condition for future wave/wind floating prototypes. Abstract: Co-located offshore wind turbines and wave energy converters are of great interests as several studies established that combined power productions are more predictable, less-fluctuating and more continuous than when wind and wave technologies are working individually. However, what happens at nearshore locations with special focus to thermal winds, has never been fully explained. The objective of the present work is to evaluate the effects of local sea winds and land breeze circulations on the wave-wind resources, proposing a method to estimate the quality of the co-exploitation by means of different multivariate techniques. The research is illustrated through a case study at the novel Marine Renewable Energy Laboratory (MaRELab, Italy), analyzing a 42-year hindcast dataset. While the bulk of the power is provided by southwest waves, the wind mostly blows from two widespread sectors, west and east-northeast, having frequencies of occurrence almost the same (i. e. 50.2% vs 49.2%). Clusters referring meteo-climatic conditions that should be dominant to maximize the advantage to combine wind and wave sources, have a total occurrence of 54.1% in sea breeze time series and 72.8% in land breeze dataset. In these situations, the combined production would be more available and less variable, leading the combined nearshore wave-wind farm more interesting.